Student - teachers’ self-assessment of their autonomy - Phan Thi Thu Nga (Ho Chi Minh City Open University Journal of Science - Social Sciences, 2015)
The pilot study presented aims at investigating how student- teachers self-assessed the influence of the portfolio on their autonomy. About 120 student-teachers participated in the portfolio, but only 94 took part in self-assessing their autonomy at the end of the testing and assessment approaches/methods course. The questionnaire of 30 items covering five subthemes like self-awareness, subject matter awareness, testing process awareness, independence of learning and study habits was used as a tool for self-assessment and instrument to collect data. The data were collected after the students submitted their portfolio. The findings indicate that although student-teachers did not highly evaluate the ways the portfolio helped them to become autonomous and their independence of learning, they were very positive in the portfolio process (the mean scores are ranged from 2.8 to 3.8 out of 5). Some suggestions for further research and the application of the portfolio are recommended at the end of this article.